2020
DOI: 10.1021/jacs.0c06577
|View full text |Cite
|
Sign up to set email alerts
|

[Cu32(PET)24H8Cl2](PPh4)2: A Copper Hydride Nanocluster with a Bisquare Antiprismatic Core

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 49 publications
0
81
0
1
Order By: Relevance
“…Very recently, Sanghwa Lee et al reported the structure of another [Cu32(PET)24H8Cl2](PPh4)2 cluster, which possesses a rare edgesharing bisquare anitiprismatic Cu14H8 core caped by Cu7(PET)11Cl and Cu2PET units. 189 [Cu18H7L10I] (L=HS(C6H4)PPh2) and [Cu25H10(SPhCl2)18] 3− hydride clusters were reported by Miguel A. Huertos et al 175 and Cunfa Sun et al 182 (Scheme 5d), respectively. The former structure consists of a Cu8 core surrounded by the remaining 10 Cu atoms that are connected to S and P atoms ( Fig.…”
Section: Hydrido Cuncsmentioning
confidence: 94%
See 1 more Smart Citation
“…Very recently, Sanghwa Lee et al reported the structure of another [Cu32(PET)24H8Cl2](PPh4)2 cluster, which possesses a rare edgesharing bisquare anitiprismatic Cu14H8 core caped by Cu7(PET)11Cl and Cu2PET units. 189 [Cu18H7L10I] (L=HS(C6H4)PPh2) and [Cu25H10(SPhCl2)18] 3− hydride clusters were reported by Miguel A. Huertos et al 175 and Cunfa Sun et al 182 (Scheme 5d), respectively. The former structure consists of a Cu8 core surrounded by the remaining 10 Cu atoms that are connected to S and P atoms ( Fig.…”
Section: Hydrido Cuncsmentioning
confidence: 94%
“…The catalytic activity of [Cu32(PET)24H8Cl2](PPh4)2 cluster has been studied for the carbonylation reaction of anilines. 189 The reaction of substituted anilines with diisopropyl azodicarboxylate in the presence of a catalyst showed 100% conversions to carbamate products (Scheme 11). Although complete aniline conversions were also reached with a copper salt and a CuPET complex as catalyst, the yields of carbamate products were significantly reduced compared to the cluster.…”
Section: 324carbonylation Reactionsmentioning
confidence: 99%
“…One benchmark example is the commercially available [Cu6H6(PPh3)6] (also called Stryker's reagent), which showed a distorted octahedral Cu6 core and could catalyze several chemical reactions including chemoselective hydrogenation of unsaturated ketones, reduction of alkenes and alkynes, and hydrogenation of CO2 [7][8][9][10]. In more recent studies, the structural determination and property investigation of a handful of copper-hydride nanoclusters (NCs), including alkynylprotected Cu53H18 [11], dithiocarbamate-protected Cu7H [12] and Cu28H15 [13], dithiophosphate-protected Cu32H20 [14] and Cu20H11 [15], thiolate-protected Cu25H10 [6], Cu32H8 [16] and Cu81H32 [17], and phosphine-protected Cu18H16 [18] and Cu25H22 [19], have mapped out rich hydride coordination modes, diverse structural constructs and atom-precise catalytic sites. Nevertheless, there remains some key issues in this research area: intrinsic instability, sensitivity towards air, limited surface modifiers, and rareness of superstructures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…While mononuclear and dinuclear gold hydride complexes have long been known, [14] no polynuclear gold hydride nanoclusters have been reported until recently [15, 16] . In contrast, numerous polynuclear copper and silver hydride clusters have been synthesized and characterized [17–25] . Syntheses of gold hydride clusters would be important to understand the interactions of nanogold with hydrogen at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] In contrast, numerous polynuclear copper and silver hydride clusters have been synthesized and characterized. [17][18][19][20][21][22][23][24][25] Syntheses of gold hydride clusters would be important to understand the interactions of nanogold with hydrogen at the atomic level. Gold hydride clusters would also provide the ultimate model systems to elucidate the mechanisms of the remarkable range of hydrogen-related reactions catalyzed by gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%